Somatosensory Cortical Electrical Stimulation After Reperfusion Attenuates Ischemia/Reperfusion Injury of Rat Brain - Wang, Liang-Chao; Wei, Wei-Yen; Ho, Pei-Chuan; Wu, Pei-Yi; Chu, Yuan-Ping; Tsai, Kuen-Jer (Frontiers in Aging Neuroscience, 2021)
Objective: Ischemic stroke is an important cause of death and disability worldwide. Early reperfusion by thrombolysis or thrombectomy has improved outcome of acute ischemic stroke. However, the therapeutic window for reperfusion therapy is narrow and adjuvant therapy for neuroprotection is demanded. Electrical stimulation has been reported to be neuroprotective in many neurological diseases. In this study, the neuroprotective effect of early somatosensory cortical electrical stimulation in acute stage of ischemia/reperfusion injury was evaluated. Methods: In this study, the rat model of transient middle cerebral artery occlusion was used to explore the neuroprotective effect and underlying mechanisms of direct primary somatosensory cortex (S1) electrical stimulation with electric current of 20 Hz, 2 ms biphasic pulse, 100 μA for 30 minutes, starting at 30 minutes after reperfusion. Results: These results showed that S1 cortical electrical stimulation after reperfusion decreased infarction volume and improved functional outcome. The number of activated microglia, astrocytes, and cleaved caspase 3 positive neurons after ischemia/reperfusion injury were reduced, demonstrating that S1 cortical electrical stimulation alleviates inflammation and apoptosis. Brain-derived neurotrophic factor (BDNF) and PI3K/Akt/mTOR signaling pathway were upregulated in the penumbra area, suggesting that BDNF/TrkB signals and their downstream PI3K/Akt signaling pathway play roles in electrical stimulation related neuroprotection. Conclusion: Therefore, this study demonstrated that somatosensory cortical electrical stimulation soon after reperfusion can attenuate ischemia/reperfusion injury and is a promising adjuvant therapy for thrombolytic treatment after acute ischemic stroke. Advanced techniques and devices for high-definition transcranial direct current stimulation still deserve further development in this regard.